GIBSON, Anne ; FAST, Thimothy. The women’s atlas of the United States - Solsona, Montserrat (Documents d’Anàlisi Geogràfica, 1989)
GIBSON, Anne & FAST, Timothy, 1986, The Women's Atlas of the United States, Nueva York/Oxford, Facts on File Publications, 248 pp.